Deregulation of Nigeria’s Natural Resources Sector as a Catalyst for National Development - Aninye, Okechukwu Iloba -; Kontagora, Abdullahi Mohammed (NIU Journal of Social Sciences; Vol 4 No 4 (2018): KIU Journal of Social Sciences, Vol. 4 No. 4, December 2018, 2019)
For over 40 years Nigeria’s economy was driven by petroleum. During this period, her influence in Africa soared. It peaked in the 1970s and 80s, so much so that she spent oil money on the decolonization of certain countries in Africa. Natural Resource in Nigeria is owned by the people, but administered for the overall benefit of Nigerians by government. This precious natural gift lost its pride of place when the worth of petroleum dipped in the international market. Prior to this economic decline, Nigeria adopted a near socialist system by operating a subsidy regime. Because what belongs to government belongs to no specific person, Nigerian past leaders became profligate. A public property is nobody’s property and can be misused and mismanaged. So, Natural Resources is a gift from God to be used to develop a given area or country for the betterment of the people. Natural Resources can be better harnessed by private enterprise. Thus, deregulation in the least, or outright privatization is the best option in maximizing natural resources. Keywords: Deregulation, Natural Resources, Exploitation of Natural Resources, National Development.